Hepatitis acute fulminant and Thyrotosicosis: Case Report - Miranda, Carla Paixão (Brazilian Journal of Transplantation, 2016)
It is presented here the case report of a 44 years old female patient admitted at the Intensive Care Unit (ICU) of the Hospital das Clínicas in Belo Horizonte/MG, with abdominal pain, nausea, vomiting, jaundice and fever, anorexia, loss of appetite, whose symptoms started 30 days before. She had a history of hypothyroidism being irregularly treated with T4 for the last five years, and her treatment was interrupted on the occasion the current symptoms appeared. She presented T3 (7.26 pg/mL) VN: 2.77 to 5.07; TSH (0.214 IU/mL) VN: 0.465. Transaminases AST (977 U/L) VN: 15 to 46; ALT (795 U/L) VN:13 to 69; bilirubin total (4.12 mg/dL) VN: 0.2 to 1.3; direct bilirubin (30 mg/dL) VN: up to 0.25. She was kept with no anti-thyroid and she started on propranolol at an up to 480 mg/day dosage. An MRI abdominal examination presented cholangiocarcinoma with free abdominal fluid, suggestive of being related to the inflammatory process. There was non-specific thickening of the gallbladder and bilateral pleural effusion. Serology examination for Hepatitis A, B, and C was negative. There was deterioration of the liver function and the high levels of thyroid hormones were kept. The patient suffered acute fulminant hepatic failure, and she was immediately submitted to hepatic transplant. After the procedure, the liver (explant) was sent for anatomopathological study; histopathologic findings included the presence of an extensive area of necrosis of the liver parenchyma. The remaining septa showed mononuclear inflammatory infiltrates (MNII). Therefore, it was concluded that chronic hyperthyroidism can exacerbate and perpetuate acute fulminant hepatic failure and the regular medical treatment, together with clinically routine laboratory examination could prevent severe complications, permitting a successful therapy in patients with hyperthyroidism.